Patient Preferences with Regard to Laser versus Intravitreal Injections in the Treatment of Diabetic Macular Edema. (4th April 2017) - Mason, Lauren; Crosson, Jason N.; Mason, John O.; McGwin, Gerald
Abstract : Purpose . To identify treatment preferences of patients with diabetic macular edema (DME) having undergone laser and intravitreal injections. Methods . Patients with DME who received lasers and injections were surveyed, measuring preferences toward specific treatments. 66/210 diabetic patients met the criteria for our survey assessing preference for lasers and/or injections, incorporating demographics and treatment preference questions. Outcome measures included treatment preference (laser or injections), how often patients are willing to be treated, and how much vision they will sacrifice to avoid being treated every month. Results . 66 patients completed the survey. The mean diabetes duration was 20.7 years, the mean retina follow-up was 4.4 years, and patients received a mean of 4.82 lasers and 4.86 injections. 56% preferred injections, 33% preferred laser, and 11% had no preference. Regarding treatment effectiveness, 38% found no difference, 36% chose laser, and 25% chose injections. Regarding anxiety, 56% reported injection anxiety. While 50% versus 38% reported that laser was easier than injections. 91% would give up zero lines on the eye chart, and 76% would come in 12 times yearly for treatment to maintain vision. Conclusion . Patients with DME have no profound preference regarding laser versus intravitreal injections but prefer aggressive treatment and are unwilling to sacrifice vision for less visits.